(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
A \((p,q)\) graph \(G\) is said to have a \(k\)-odd edge mean labeling \((k1)\), if there exists an injection \(f\) from the edges of \(G\) to \({0,1,2,3,…,2k+2p-3}\) such that the induced map \(f^*\) defined on \(V\) by \(f^* (v)=f(vu) (v) ceil\) is a bijection from \(V\) to \({2k-1,2k+1,2k+3,…, 2k+2p-3}\). A graph that admits a \(k\)-odd edge mean labeling is called a \(k\)-odd edge mean graph. In this paper, we have introduced \(k\)-odd edge mean labeling and we have investigated the same labeling for basic graphs like path and star. Also we have examined the existence and non existence of cycles.